2007
DOI: 10.1016/j.amepre.2006.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Correlates of Physical Activity and Nutrition Behaviors in Adolescents

Abstract: Background-Knowledge of the prevalence, clustering, and correlates of multiple adolescent health behaviors can inform the design of health promotion interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
155
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(183 citation statements)
references
References 26 publications
24
155
1
3
Order By: Relevance
“…Similar to the improved nutrition result, this also suggests a stepwise improvement in physical activity when diet quality increased from poor to average to superior; thus, students with the highest activity levels also had the highest diet quality scores. This suggests a clustering of positive lifestyle behaviours, which is consistent with previous reports from both Canada (41) and the USA (6,44,45) . Although socioeconomic status (SES) was not measured in the current study, results from a previous web-based survey indicated vegetable and fruit, fibre and breakfast consumption increased with increasing income, and that consumption of added sugar decreased (13) .…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the improved nutrition result, this also suggests a stepwise improvement in physical activity when diet quality increased from poor to average to superior; thus, students with the highest activity levels also had the highest diet quality scores. This suggests a clustering of positive lifestyle behaviours, which is consistent with previous reports from both Canada (41) and the USA (6,44,45) . Although socioeconomic status (SES) was not measured in the current study, results from a previous web-based survey indicated vegetable and fruit, fibre and breakfast consumption increased with increasing income, and that consumption of added sugar decreased (13) .…”
Section: Discussionsupporting
confidence: 92%
“…Few studies have examined adolescents' dietary patterns using factor analysis (4)(5)(6) . While lower socio-economic status (7) , overweight (8) , sedentary behaviours (9) and parental smoking (10) have been linked to poorer diet quality in children, these have not been widely examined in relation to adolescents' dietary patterns. Identifying factors that influence the dietary patterns of adolescents may assist in targeting at-risk groups and developing strategies to improve dietary intakes.…”
mentioning
confidence: 99%
“…Previous research on adolescent fat intake has engaged predominantly White samples (Neumark-Sztainer, Story, & Perry, 2001;Sanchez et al, 2007;Stanton, Fries, & Danish, 2003;Zabinksi et al, 2006). Moreover, results regarding the relationship between age and total fat intake have been mixed, making comparisons between findings from this study and findings from previous research difficult.…”
Section: Discussionmentioning
confidence: 99%